Biographies of Working Men - Allen, Grant, 1848-1899 (Salt Lake City, UT : Project Gutenberg, 2003)
"Biographies of Working Men" by Grant Allen is a collection of biographical sketches written in the late 19th century. The work chronicles the lives of notable individuals from humble beginnings who rose to prominence through their hard work and determination. The first chapter focuses on Thomas Telford, a stonemason who became a celebrated engineer, showcasing the theme of perseverance and the transformative power of education and ambition. At the start of the text, the author describes the desolate and rugged landscape of Eskdale, Scotland, where Thomas Telford was born into a poor family. Following the death of his father, Telford's mother worked tirelessly to support him, instilling in him both a strong work ethic and an appreciation for learning. Despite his harsh upbringing, Telford demonstrated a passion for engineering from a young age. The narrative unfolds his early life, detailing his education, his apprenticeship as a stonemason, and the influence of literature and early work experiences that shaped his future success as a pioneering figure in British civil engineering, ultimately working on significant projects like the holyhead Road and the Menai Suspension Bridge. Through this portrayal, the opening portion sets a tone of inspiration and hope for readers, highlighting the potential for greatness that lies within individuals, regardless of their origins. (This is an automatically generated summary.)
Thomas Telford, stonemason -- George Stephenson, engine-man -- John Gibson, sculptor -- William Herschel, bandsman -- Jean François Millet, painter -- James Garfield, canal boy -- Thomas Edward, shoemaker.
Release date is 2003-10-01
Produced by Charles Aldarondo. HTML version by Al Haines.
Keywords: Labor -- Biography; Biography -- 19th century; Working class -- Biography